2013
DOI: 10.4028/www.scientific.net/amr.802.179
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Hardness of Cu-Zn-Si-Al-Sn Brasses with Antimony Addition

Abstract: The objective of this work is to study the effect of antimony on as-cast microstructures and hardness of dual phase brassed. The studied compositions consisted of 56Cu-(42-X)Zn-1Si-0.5Al-0.5Sn-(X)Sb with varied antimony content in the range of 0.5-2.0 wt%. The alloys were prepared by melting pure elements using an induction furnace in graphite crucible at the temperature about 1,200 °C. The chemical composition of each alloy has been analyzed by X-ray fluorescence (XRF). Microstructures of the as-cast ingots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Sample B1 (Cu-Zn-AL) structure was changed and became refined due to the addition of Al, which plays an essential parameter in increasing Zn concentration (Zn equivalent); increasing Zn % will refine the grains [26]. While Figure (8), which represented sample B2 (Cu-Zn-Al-Sn), the presence of Sn plays an essential role in changing the shape of microstructure; it prevents dendrite growth and increases refining; accordingly, the existence of an element (AI, Sn) will enhance solid solution strengthening, an increase in mechanical properties will be observed, for this reason, ductility of brass will decrease [27]. A change also occurs in the microstructure for specimen B3 (Cu-Zn-Al-Ge); the structure will change: equiaxed grain will appear due to the precipitation of free particles of Ge element on grain boundaries [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sample B1 (Cu-Zn-AL) structure was changed and became refined due to the addition of Al, which plays an essential parameter in increasing Zn concentration (Zn equivalent); increasing Zn % will refine the grains [26]. While Figure (8), which represented sample B2 (Cu-Zn-Al-Sn), the presence of Sn plays an essential role in changing the shape of microstructure; it prevents dendrite growth and increases refining; accordingly, the existence of an element (AI, Sn) will enhance solid solution strengthening, an increase in mechanical properties will be observed, for this reason, ductility of brass will decrease [27]. A change also occurs in the microstructure for specimen B3 (Cu-Zn-Al-Ge); the structure will change: equiaxed grain will appear due to the precipitation of free particles of Ge element on grain boundaries [28].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to an increased solid solution strengthening effect taking place due to the incorporation of Sb within the γ phase. Nonetheless, upon reaching 2.0 wt.% Sb content, a high-Sb intermetallic phase would form, reducing the hardness of the investigated alloying system by roughly 17% [73]. Chandra et al found that both the ductility as well as the flow stress of α-β brass is significantly affected by the addition of Cerium (Ce) [74].…”
Section: Novel Lead-free Brassesmentioning
confidence: 99%
“…The zinc-antimony (Zn-Sb) binary system is one of the best thermoelectric materials due to its low lattice thermal conductivity which is stable at intermediate temperatures. 14,15 This alloy contains a higher degree of atomic disorder within the whole concentration. Doping of Cu in the Zn-Sb alloys enhances the whole concentration, and leads to the higher carrier concentration.…”
Section: Introductionmentioning
confidence: 99%